Dental Health Promotion Using Snakes and Ladder Media on the Knowledge of Teeth Brushing of Grade II Students of MIN 8 Padang Lawas Utara - Buwana Dhewi, Shiska; Kartika Emailijati (PT Inovasi Pratama Internasional, 2025)
Dental health is an integral part of overall general health, and it is important to instill it early on, especially in elementary school children. One effective way to increase children's awareness and knowledge about the importance of brushing their teeth properly is through fun and easy-to-understand health education and promotion. This study aims to determine the effectiveness of the snakes and ladders game media in increasing knowledge of brushing teeth in grade II students of MIN 8 Padang Lawas Utara. This study used a descriptive design with a pretest and posttest approach involving all grade II students as a sample (total sampling). Data were collected by administering questionnaires before and after the implementation of the snakes and ladders game that had been modified with dental health education content. The results showed that before health promotion using snakes and ladders media, the majority of students had a level of knowledge in the moderate and poor categories, each of which was 14 people (46.66%), and only 2 people (6.66%) were in the good category. However, after being given an intervention in the form of an educational snakes and ladders game, all students (100%) experienced a significant increase in knowledge, all of which were in the good category. This shows that the use of educational game media such as snakes and ladders is very effective in conveying dental health information in a fun and easy-to-understand way for children. This study provides a positive contribution in developing innovative, interesting, and appropriate dental health promotion methods for elementary school children, and can be applied in elementary school environments as alternative learning media.